Lisianthus Vase Life after 1-Methylcyclopropene and Salicylic Acid Postharvest Treatment - Cavasini, R. [UNESP]; Laschi, D. [UNESP]; Favero, B. T. [UNESP]; Lima, G. P. P. [UNESP]; Castro, ACR; Cuquel, F. L.; Loges, V (Int Soc Horticultural Science, 2015)
This study evaluated the effects of application of 0.5 mu l L-1 1-methyl-cyclopropene (1-MCP), 1000 mg L-1 salicylic acid (SA) and the interaction between the two products at room temperature and pre-exposure at 9 +/- 2 degrees C for 24 h in maintaining postharvest quality of lisianthus flowers. After applying the treatment, the flowers were kept in jars with water, stored at 24 +/- 2 degrees C. The SA treatments proved ineffective, presenting symptoms of phytotoxicity, with high rate of bent neck and yellowing of petals, both at room temperature and in cold storage, and propitiate the emergence of pathogens. The association between 1-MCP in pre-exposure to 9 +/- 2 degrees C for 24 h increased the durability of the stems in six days compared to the control treatment, with less symptoms of bent neck and swelling of stems.
Keywords: Eustoma grandiflorum; phytotoxicity; 1-MCP